Henoch-Schönlein purpura with c-ANCA antibody in an adult - Pedro de Freitas Silva Torraca; Bruna Corrêa de Castro; Günter Hans Filho (Sociedade Brasileira de Dermatologia, 2016)
Abstract: The Henoch-Schönlein purpura is the vasculitis associated with deposits of immunoglobulin A in small vessels. Its association with cytoplasmic antineutrophil cytoplasmic antibodies is possible, but rare. This vasculitis is uncommon in adults and the main clinic manifestations are purpuric lesions in lower limbs with gastrointestinal symptoms and renal involvement. The present work describes a rare case of Henoch-Schönlein purpura in an adult with cytoplasmic antineutrophil cytoplasmic antibodies.